A highly efficient photoelectrochemical H2O2 production reaction with Co3O4 as a co-catalyst. Issue 51 (6th June 2018) - Zhang, Jijie; Chang, Xiaoxia; Luo, Zhibin; Wang, Tuo; Gong, Jinlong
Abstract : This communication describes an efficient co-catalyst Co3 O4 nanoparticle with a tunable two-electron water oxidation reaction pathway in photoelectrochemical H2 O2 production. Abstract : This communication describes an efficient co-catalyst Co3 O4 nanoparticle with a tunable two-electron water oxidation reaction pathway in photoelectrochemical H2 O2 production. The photoluminescence measurement explains that the promotion effect is due to the accelerated activation of water to ˙OH. The increased Faraday efficiency of H2 O2 for the Co3 O4 /WO3 sample also verifies that the promotion effect to a two-electron water oxidation reaction of Co3 O4 is universal to other semiconductor photoanodes.